High-Gradient Magnetic Separation Method for Weakly Magnetic Particles: an Industrial Application - Chouki, Farsi (Université de M'sila, 2019)
The high-gradient magnetic separation process is a technique used in heavy industries, particularly steel mills, to extract magnetic particles from mix-tures. The difficulty of separating the slightly magnetic particles from the nonmagnetic ones lies in the distribution of the magnetic field and the fine-ness of their class to be separated. A use of different separation matrix pro-file is implemented, making it possible to act on the value of the gradient of the inhomogeneous magnetic field. Different matrixes are tested and the re-sults obtained experimentally allows to choose the most efficient matrix form in the operation of extraction which increased by 11% in magnetic fraction yield, 15% iron content and 17% of extraction degree relative to the John’s matrix. This matrix used is consistent with that cited in literatures. The sep-aration technology used can extend its useful application to small particles from very weakly magnetic materials. Its exploitation will result in the method of reducing the degree of pollution and improvement the process of extraction of minerals that has an impact on the environment and on human
Keywords: magnetic matrix, high-gradient magnetic separation process (HGMS), gradient of magnetic field, magnetic particles.